Record Provisions of Freight Trains’ Fractional Numbers in Terms of Hardware-Software Complex Elborus Based Automated Train Timing - V. Yu. Kiryakin; A. V. Novgorodtseva (Вестник Научно-исследовательского института железнодорожного транспорта, 2015)
The JSC VNIIZhT experts are engaged in introduction process of hardware-software complex (HSC) ELBRUS intended for automated production of living train diagrams for railway domains. While preparing tight run profiles numbers of trains which will adhere to the schedules of this train diagram are not uniquely determined beforehand. To make possible use of the same train paths by various type trains several numbers are assigned to each train one of which is basic and others - fractional. One of the most significant modules of the HSC ELBRUS mathematical model implements recording function of fractional numbers in the train diagram. The paper describes in detail basic development principles of this module’s operating procedures in the mathematical model HSC ELBRUS environment.